MORFOMETRI DAUN Rhizophora mucronata DI PULAU TEMUDONG DAN PULAU KERAMAT KECAMATAN UTAN SUMBAWA NTB - Salsabila, Nandita Pasya; Latifah, Sitti; Hidayati, Eni (JURNAL RIMBA LESTARI, 2022)
Leaf morphometric is the leaf length and width ratio that become one of the mangrove health indicators. This study aims to compare the leaf morphometric variations of Rhizophora mucronata on Temudong and Keramat Islands in Labuhan Bajo Village, Utan District, Sumbawa. Determination of the sample point is done using purposive sampling. As many as 40 leaves were taken that had a perfect shape. The petiole measurement on Temudong and Keramat Island obtained were as many as two (2) variations. The leaf morphometry variations ranging from 1 to 2 indicated that the health condition of Rhizophora mucronata on both islands was not disturbed. This condition is supported by the water quality of Temudong, where the temperature range between 29-34Â°C; water pH 7,6-7,8, salinity 30-32 ppt, and DO 2,15-3,24 mg/l. While in Keramat Island, the temperature range between 29,4-29,9Â°C; water pH 7,29-7,42, salinity 30-32 ppt, and DO 2,26-4,31 mg/l.